Racial diversity in mortality and morbidity in urban patients with hepatitis C. Issue 6 (28th January 2016) - Stubbs, A.; Naylor, P.; Ravindran, K.; Benjaram, S.; Reddy, N.; Mutchnick, S.; May, E.; Ehrinpreis, M.; Mutchnick, M.
Summary: Defining mortality for Caucasians and African American patients with chronic hepatitis C with respect to racial diversity is critical for counselling patients on therapy options. The objective of this study was to define racial diversity influence on mortality and morbidity of 3724 consecutive hepatitis C virus (HCV)‐infected patients seen in an urban clinic between 1995 and 2008. Mortality, as of 2011, was defined using the SSA National Death Index and correlated with early visit medical information. The HCV chronically infected patient population consisted of 2879 African Americans (AA), 758 Caucasians and 87 other, and the majority were not treated for their infection prior to 2011. The average time to death from first visit was 5 years, the average age at death was 55 years, and despite racial diversity, AA were just as likely to be reported dead as Caucasians (23% AA vs 22% Caucasians). Cirrhosis and fibrosis (liver biopsy, AST Platelet Ratio Index or Fibrosis‐4) at first visit as well as low albumin, diabetes, renal impairment and cardiac symptoms were associated with increased mortality. Treated patients who cleared the virus (sustained viral response (SVR); AA = 59; Caucasians = 40) had lower mortality than patients who were not treated (AA: 5% vs 27%; Caucasians 5% vs 26%). Hence, we find that race is not a factor in the early mortality of patients with chronic HCV infection and achieving a SVR reduced mortality. Unexpectedly, nonresponding AA also benefited by a lower mortality. African American patients with kidney disease and low albumin were at highest risk and should be treated as soon as identified.